Update - Ethical standards in sport and exercise science research - Harriss, D. J.; Atkinson, G. (International Journal of Sports Medicine, 2011)
For research that involves human participants or animals to be published in the International Journal of Sports Medicine (IJSM), it must have been conducted in accordance with recognised ethical standards and national/international laws. Authors are required to confi rm that these standards and laws have been adhered to by formally citing this editorial within the methods section of their own manuscript. In the IJSM editorial, Ethical Standards in Sport and Exercise Science Research [ 4 ] , published in 2009, we outlined the principles of the World Medical Association Declaration of Helsinki [ 2 ] and the Institute for Laboratory Animal Research of the National Research Council`s Guide for the Care and Use of Laboratory Animals [ 6 ] . We also highlighted the ethical issues that are incorporated into national/international laws and provided specifi c guidance on ethical issues which commonly arise in Sports Medicine research. These principles and issues are reproduced below from the 2009 IJSM Editorial [ 4 ] . However, we have also now updated this information in order to: A. Specifically recognise the ethical principles of professional associations and treaties when conducting research involving human participants. B. Provide specific information on key ethical issues in research involving human participants, which were briefly covered in the original IJSM editorial [ 4 ] . C. Include information on the eighth edition of the Guide for the Care and Use of Laboratory Animals [ 7 ] , published in 2010. D. Highlight the importance of optimum statistical power for human and animal research in sports medicine.